Ultra-long durable UV coating of proportional valve element armature and preparation method of ultra-long durable UV coating
By combining modified polypropylene fibers, hydroxylated carbon nanotubes and antioxidants, a UV coating with high wear resistance and oxidation resistance is formed, solving the durability problem of proportional valve core armatures and achieving ultra-long durability and high wear resistance.
Patent Information
- Application Number
- CN202411542279.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-31
AI Technical Summary
During long-term use, the proportional valve valve core armature is worn and corroded due to mechanical movement, chemical action of hydraulic oil and high temperature, and traditional coating technology is difficult to meet its durability requirements.
Using modified polypropylene fibers, hydroxylated carbon nanotubes and tris(4-chlorophenyl)methane, the combination of modified polytetrafluoroethylene and antioxidants is used to form a grid framework structure and rigid molecular chain to enhance the The coating has oxidation resistance and wear resistance, and the dispersion of magnetic fillers is improved through coupling agents, meeting the requirements of hysteresis and balance.
The ultra-long durability and high wear resistance of UV coatings are achieved, the strength and deformation resistance of polytetrafluoroethylene materials are enhanced, the service life is extended, and the stable performance is maintained at high temperatures and high loads.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to an ultra-long-lasting UV coating of a proportional valve core armature and a preparation method thereof. Background Art
[0002] During long-term use, the valve core and armature of the proportional valve will gradually wear or corrode due to repeated mechanical movement, chemical action of hydraulic oil, and high temperature in the working environment. This will not only lead to the degradation of the performance of the valve core and armature, but may also cause failure of the entire hydraulic system. Traditional solutions include the use of high-performance materials and traditional coating technologies, but these methods often cannot meet the growing durability requirements.
[0003] UV curing coating technology has received extensive attention in industrial applications due to its advantages such as fast curing, environmental protection, and energy saving. UV coating can form a dense protective film on the surface of the proportional valve spool armature to improve its durability. However, in order to meet the requirements of higher durability, traditional UV coating still needs further improvement.
[0004] Chinese patent CN 111744751 A relates to a surface microstructure finishing process of a self-matting UV coating and its application. The raw materials for preparing the UV coating include the following components by weight percentage: 30-50% silicon-modified polyurethane acrylate oligomer, 10-25% polyurethane acrylate oligomer, 0.1-4% wear-resistant micropowder, 20-40% active diluent, 0-40% organic solvent, 1-5% initiator, and 0.1-0.5% dispersant. The UV coating of this invention has excellent hardness, anti-fouling, weather resistance, wear resistance and self-matting properties, and realizes the ultra-matte and high-quality imitation 3D glass effect of the back cover plate of the mobile phone. However, when used for the valve core armature of the proportional valve, its wear resistance and durability are still difficult to meet the requirements.
[0005] Therefore, there is an urgent need for a UV coating for the valve core armature of a proportional valve, which has both wear resistance and ultra-long durability. Summary of the invention
[0006] In view of the existing technical problems, the purpose of the present invention is to provide an ultra-durable UV coating for a proportional valve core armature and a preparation method thereof. The UV coating of the present invention has good oxidation resistance and wear resistance, and can meet the balanced requirements of the proportional valve for hysteresis.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] On the one hand, the present invention provides an ultra-long-lasting UV coating for a proportional valve spool armature. The coating comprises the following raw materials, measured in parts by weight: 12-24 parts of diisocyanate, 40-60 parts of polytetramethylene ether glycol, 5-10 parts of hydroxyethyl acrylate, 4-8 parts of hydroxyethyl methacrylate, 10-25 parts of isobornyl acrylate, 8-16 parts of alkyl acrylate, 3-8 parts of modified magnetic filler, 3-6 parts of modified polytetrafluoroethylene, 1-3 parts of photoinitiator, 1-2 parts of antioxidant, and 0.1-0.2 parts of colorant.
[0009] The reaction mechanism and effects of the present invention are as follows:
[0010] 1. The unique molecular structure of polytetrafluoroethylene brings a certain degree of wear resistance, but it may still deform or wear under high loads, which limits its wear resistance.
[0011] The present invention improves the wear resistance of polytetrafluoroethylene by introducing modified polypropylene fiber and hydroxylated carbon nanotubes. First, after being modified by a silane coupling agent, it not only helps to improve the compatibility of polypropylene fiber with polytetrafluoroethylene matrix, but also can make the surface of polypropylene fiber rough. After adding hydroxylated carbon nanotubes, a part of hydroxylated carbon nanotubes is efficiently attached to the surface of modified polypropylene fiber by physical adsorption, and another part is chemically bonded to the surface of modified polypropylene fiber to form a grid skeleton structure as a whole, and polytetrafluoroethylene is filled into hydroxylated carbon nanotubes by stirring and grinding, thereby avoiding the problem of poor interface compatibility between hydroxylated carbon nanotubes and polytetrafluoroethylene. Secondly, the modified polypropylene fiber has a good thermodynamic match with the polytetrafluoroethylene matrix. At the same time, the unique hollow structure and excellent physical properties of the hydroxylated carbon nanotubes have significant potential in improving the wear resistance of polytetrafluoroethylene. The applicant limits the mass ratio between the modified polypropylene fiber, the hydroxylated carbon nanotubes and the polytetrafluoroethylene to synergistically promote the modification of the polytetrafluoroethylene, thereby improving the strength and deformation resistance of the modified polytetrafluoroethylene material, enhancing the wear resistance of the modified polytetrafluoroethylene material, extending the service life of the polytetrafluoroethylene material, and ensuring its long-term stability, thereby improving the wear resistance and stability of the UV coating.
[0012] 2. Hindered phenol antioxidants are widely used due to their excellent performance, high thermal stability, low toxicity, etc. However, these antioxidants usually have a small relative molecular mass, which makes them easy to volatilize or be extracted during use due to poor extraction resistance, resulting in a decrease in their antioxidant performance and physical losses. The applicant introduced tris(4-chlorophenyl)methane to form a rigid structure, which makes it highly symmetrical and has a high regularity. The free rotation of the molecular chain is affected by the increase in the rigid structure, making it difficult for the molecular configuration to change, thereby effectively improving the thermal stability and migration resistance of the antioxidant, allowing it to play a long-term and stable antioxidant role; in addition, the acyl chloride groups produced by the reaction also help to improve the antioxidant performance, thereby making the UV coating last longer and the ultra-long durability better.
[0013] 2. The present invention adopts a coupling agent to modify the magnetic filler, thereby improving the dispersibility of the magnetic filler, which is beneficial to meeting the balance requirements of the proportional valve for hysteresis.
[0014] In some embodiments, the method for preparing the modified magnetic filler comprises the following steps:
[0015] The magnetic filler and anhydrous ethanol are mixed, a coupling agent is added, the mixture is heated to 50-65° C., and the mixture is stirred for reaction for 2-4 hours; the mixture is cooled, filtered, and dried to obtain a modified magnetic filler.
[0016] In some embodiments, the magnetic filler is any one or more of iron oxide powder, ferroferric oxide powder, nickel powder, and cobalt powder.
[0017] In some embodiments, the mass ratio of the magnetic filler to the coupling agent is 1:(1-1.2).
[0018] In some embodiments, the method for preparing the modified polytetrafluoroethylene comprises the following steps:
[0019] S1. The silane coupling agent and anhydrous ethanol are mixed, stirred, added to the polypropylene fiber, soaked, filtered, washed, and dried to obtain a modified polypropylene fiber;
[0020] S2. The modified polypropylene fiber, hydroxylated carbon nanotubes and anhydrous ethanol obtained in step S1 are mixed, heated and stirred to obtain a mixed solution;
[0021] S3. Add polytetrafluoroethylene to the mixed solution obtained in step S2, stir, grind, and spray-dry to obtain modified polytetrafluoroethylene.
[0022] In some embodiments, the mass ratio of the modified polypropylene fiber to the hydroxylated carbon nanotubes in step S2 is (1.3-2):1.
[0023] In some embodiments, the mass ratio of polytetrafluoroethylene to the hydroxylated carbon nanotubes in the mixed solution in step S3 is (8-11):1.
[0024] In some embodiments, the method for preparing the antioxidant comprises the following steps:
[0025] Q1. Add 3,5-di-tert-butyl-4-hydroxybenzoic acid and chloroform into a reaction kettle, add dichlorothionyl dropwise under an inert gas atmosphere, heat to 45-55°C, react at a constant temperature for 5-6 hours, and distill under reduced pressure to obtain 3,5-di-tert-butyl-4-hydroxybenzoyl chloride;
[0026] Q2. Add 3,5-di-tert-butyl-4-hydroxybenzoyl chloride, tri(4-chlorophenyl)methane and sodium hydroxide obtained in step Q1 into the reaction kettle in sequence, heat to 30-45°C and react for 4-8h, cool, wash and dry to obtain an antioxidant.
[0027] In some embodiments, the molar ratio of 3,5-di-tert-butyl-4-hydroxybenzoic acid to tris(4-chlorophenyl)methane is (3.2-3.8):1.
[0028] In some embodiments, the colorant is any one or more of titanium dioxide, chromium oxide green, cobalt blue, inorganic brown and zinc chrome yellow.
[0029] In some embodiments, the diisocyanate is selected from any one or more of isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate and toluene diisocyanate.
[0030] Another aspect of the present invention provides a method for preparing an ultra-long-lasting UV coating of a proportional valve spool armature, comprising the following steps:
[0031] 1. mixing diisocyanate, polytetramethylene glycol, hydroxyethyl acrylate, hydroxyethyl methacrylate, isobornyl acrylate, alkyl acrylate, modified magnetic filler, modified polytetrafluoroethylene, photoinitiator, antioxidant and colorant to obtain a primary mixture;
[0032] 2. Grind the primary mixture obtained in step 1 by a three-roll mill, spray or apply it on the valve core armature of the proportional valve, and cure it by UV to obtain a UV coating.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The UV coating of the present invention has good oxidation resistance and wear resistance, and can meet the balance requirements of the proportional valve for hysteresis.
[0035] 2. The present invention improves the wear resistance of polytetrafluoroethylene by introducing modified polypropylene fibers and hydroxylated carbon nanotubes, which not only improves the interface compatibility between hydroxylated carbon nanotubes and polytetrafluoroethylene, but also improves the strength, deformation resistance and wear resistance of the modified polytetrafluoroethylene material, thereby improving the wear resistance of the UV coating.
[0036] 3. The present invention can effectively improve the thermal stability and migration resistance of the antioxidant by introducing tri(4-chlorophenyl)methane to form a rigid structure, so that it can play an antioxidant role stably for a long time; in addition, the acyl chloride group generated by the reaction also helps to improve the antioxidant performance. DETAILED DESCRIPTION
[0037] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, rather than to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0038] According to the ratios of the raw materials and the preparation methods specified in the following examples and comparative examples, various UV coatings were prepared.
[0039] In order to facilitate those skilled in the art to implement the present invention, some raw material manufacturers of the embodiments and comparative examples are described as follows:
[0040] Polytetramethylenetetrahydrofuran ether glycol: purchased from Jinan Yuyi Chemical Co., Ltd., model PTMG-1000;
[0041] Polytetrafluoroethylene: purchased from Dongguan Zhengtao Plastic Co., Ltd., model F-201;
[0042] Polypropylene fiber: purchased from Dacheng County Yibo Chemical Co., Ltd.
[0043] Other raw materials are not specially specified and can be purchased from the market.
[0044] Preparation Example 1
[0045] The preparation method of modified polytetrafluoroethylene comprises the following steps:
[0046] S1. 24 g of 3-(methacryloyloxy)propyltrimethoxysilane and 1600 mL of anhydrous ethanol were mixed and stirred for 1 h, 200 g of polypropylene fiber was added, soaked for 45 min, filtered, washed with deionized water 3 times, and dried at 100 ° C for 3 h to obtain modified polypropylene fiber;
[0047] S2. 165 g of modified polypropylene fiber obtained in step S1, 100 g of hydroxylated carbon nanotubes, and 2 L of anhydrous ethanol were mixed, heated to 55 ° C, and stirred for 3 h to obtain a mixed solution;
[0048] S3. Add 950 g of polytetrafluoroethylene to the mixed solution obtained in step S2, stir for 2 h, grind for 30 min, and spray dry to constant weight at 150° C. and a spray pressure of 2 MPa to obtain modified polytetrafluoroethylene.
[0049] Preparation Example 2
[0050] The preparation method of modified polytetrafluoroethylene is the same as that of Preparation Example 1, except that the added amount of modified polypropylene fiber is 120 g.
[0051] Preparation Example 3
[0052] The preparation method of modified polytetrafluoroethylene is the same as that of Preparation Example 1, except that the amount of polytetrafluoroethylene added is 780 g.
[0053] Preparation Example 4
[0054] The preparation method of antioxidant A comprises the following steps:
[0055] Q1. Add 0.02 mol 3,5-di-tert-butyl-4-hydroxybenzoic acid and 50 mL chloroform into a reactor, add 8 mL thionyl chloride dropwise under a nitrogen atmosphere, heat to 50°C, react at a constant temperature for 5.5 hours, and distill under reduced pressure to obtain 3,5-di-tert-butyl-4-hydroxybenzoyl chloride;
[0056] Q2. 0.01 mol 3,5-di-tert-butyl-4-hydroxybenzoyl chloride, 0.035 mol tri(4-chlorophenyl)methane and 25 mL 0.2 mol / L sodium hydroxide aqueous solution obtained in step Q1 were added into the reactor in sequence, heated to 35°C for reaction for 6 h, cooled to room temperature, washed with deionized water until neutral, and vacuum dried at 85°C for 8 h to obtain antioxidant A.
[0057] Preparation Example 5
[0058] The preparation method of antioxidant B is the same as that of Preparation Example 4, except that the amount of tri(4-chlorophenyl)methane added is 0.029 mol.
[0059] Preparation Example 6
[0060] The preparation method of the modified magnetic filler comprises the following steps:
[0061] 500 g of iron oxide powder and 2 L of anhydrous ethanol were mixed, 550 g of 3-(methacryloyloxy)propyltrimethoxysilane was added, the mixture was heated to 60° C., stirred for reaction for 3 h, cooled to room temperature, filtered, and dried at 85° C. to constant weight to obtain a modified magnetic filler.
[0062] Example 1
[0063] The invention discloses an ultra-long-lasting UV coating for a proportional valve core armature. The coating comprises the following raw materials, measured in parts by weight: 18 parts of isophorone diisocyanate, 50 parts of polytetramethylene ether glycol, 7.5 parts of hydroxyethyl acrylate, 6 parts of hydroxyethyl methacrylate, 18 parts of isobornyl acrylate, 12 parts of dodecyl acrylate, 5.5 parts of modified magnetic filler, 4.5 parts of modified polytetrafluoroethylene A, 2 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 1.5 parts of antioxidant A and 0.15 parts of titanium dioxide.
[0064] The preparation method of the UV coating of this embodiment comprises the following steps:
[0065] 1. Mix isophorone diisocyanate, polytetramethylene ether glycol, hydroxyethyl acrylate, hydroxyethyl methacrylate, isobornyl acrylate, alkyl acrylate, modified magnetic filler, modified polytetrafluoroethylene A, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, antioxidant A, and titanium dioxide to obtain a primary mixture;
[0066] 2. Grind the primary mixture obtained in step 1 with a three-roll mill, apply it to the armature of the proportional valve core, and cure it with UV to obtain a UV coating.
[0067] Example 2
[0068] The invention discloses an ultra-long-lasting UV coating for a proportional valve core armature. The coating comprises the following raw materials, measured in parts by weight: 12 parts of isophorone diisocyanate, 40 parts of polytetramethylene ether glycol, 5 parts of hydroxyethyl acrylate, 4 parts of hydroxyethyl methacrylate, 10 parts of isobornyl acrylate, 8 parts of dodecyl acrylate, 3 parts of modified magnetic filler, 3 parts of modified polytetrafluoroethylene A, 1 part of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 1 part of antioxidant A and 0.1 part of titanium dioxide.
[0069] The preparation method of the UV coating of this embodiment is the same as that of embodiment 1.
[0070] Example 3
[0071] The invention discloses an ultra-long-lasting UV coating for a proportional valve core armature. The coating comprises the following raw materials, measured in parts by weight: 24 parts of isophorone diisocyanate, 60 parts of polytetramethylene ether glycol, 10 parts of hydroxyethyl acrylate, 8 parts of hydroxyethyl methacrylate, 25 parts of isobornyl acrylate, 16 parts of dodecyl acrylate, 8 parts of modified magnetic filler, 6 parts of modified polytetrafluoroethylene A, 3 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 2 parts of antioxidant A and 0.2 parts of titanium dioxide.
[0072] The preparation method of the UV coating of this embodiment is the same as that of embodiment 1.
[0073] Example 4
[0074] An ultra-long-lasting UV coating for a proportional valve core armature and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal amount of modified polytetrafluoroethylene B is used to replace modified polytetrafluoroethylene A.
[0075] Example 5
[0076] An ultra-long-lasting UV coating for a proportional valve core armature and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal amount of modified polytetrafluoroethylene C is used to replace modified polytetrafluoroethylene A.
[0077] Example 6
[0078] An ultra-long-lasting UV coating for a proportional valve core armature and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal amount of antioxidant B is used to replace antioxidant A.
[0079] Example 7
[0080] An ultra-long-lasting UV coating for a proportional valve core armature and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal amount of 2,6-di-tert-butyl-4-methylphenol is used to replace antioxidant A.
[0081] Comparative Example 1
[0082] An ultra-long-lasting UV coating for a proportional valve core armature and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal amount of commercially available polytetrafluoroethylene is used to replace modified polytetrafluoroethylene A.
[0083] Effect evaluation:
[0084] The UV coatings prepared in the above Examples 1-7 and Comparative Example 1 were tested and analyzed, and the specific results are shown in Table 1.
[0085] Performance Testing:
[0086] (1) Wear resistance: UV coating was applied to the armature of the proportional valve core with a coating thickness of 0.1 mm. After UV curing, the dynamic friction coefficient was measured after 1000 reciprocating cycles under the test conditions of a vertical load of 1 kg and a reciprocating movement of 10 cm at a frequency of 10 Hz.
[0087] (2) Antioxidation: The UV coating was applied to the upper surface of a steel material with a size of 10 cm*5 cm*0.1 cm (length*width*height) with a coating thickness of 0.05 mm. After UV curing, it was placed in an oven at 120°C for 6 h. After cooling to room temperature, it was placed in an environment with a humidity of 80% for 6 h. It was taken out and placed in an environment with a humidity of 40% at normal temperature and pressure for one week to observe whether the coating had any cracking.
[0088] Table 1 Performance test
[0089] Serial number Dynamic friction coefficient Coating cracking Example 1 0.43 No cracking Example 2 0.48 No cracking Example 3 0.45 No cracking Example 4 0.54 No cracking Example 5 0.58 No cracking Example 6 0.44 Slight cracking Example 7 0.45 There is cracking Comparative Example 1 0.68 No cracking
[0090] The results in Table 1 show that the UV coatings prepared in Examples 1-3 have good oxidation resistance and wear resistance. The coatings in Examples 1-3 have no cracking after testing, indicating good oxidation resistance, and thus the longer the UV coating lasts, the better the ultra-long durability.
[0091] Compared with Example 1, when preparing modified polytetrafluoroethylene, Example 4-5 changes the mass ratio of modified polypropylene fiber and hydroxylated carbon nanotubes, and the attachment amount of hydroxylated carbon nanotubes is reduced; Example 5 changes the mass ratio of polytetrafluoroethylene and hydroxylated carbon nanotubes in the mixed liquid, and the synergistic effect is weakened, both of which affect the wear resistance of the UV coating; Comparative Example 1 replaces modified polytetrafluoroethylene A with an equal amount of commercially available polytetrafluoroethylene, and the UV coating wears under high load, and the dynamic friction coefficient increases.
[0092] Compared with Example 1, Example 6-7 changes the molar ratio of 3,5-di-tert-butyl-4-hydroxybenzoic acid and tri(4-chlorophenyl)methane when preparing the antioxidant, and loses the rigid structure; Example 7 uses an equal amount of 2,6-di-tert-butyl-4-methylphenol to replace antioxidant A, which has a small molecular weight. Both of them will reduce the antioxidant properties of the UV coating.
[0093] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.
Claims
1. An ultra-long-lasting UV coating for a proportional valve spool armature, characterized in that: The coating comprises the following raw materials, in parts by weight: 12-24 parts of diisocyanate, 40-60 parts of polytetramethylene ether glycol, 5-10 parts of hydroxyethyl acrylate, 4-8 parts of hydroxyethyl methacrylate, 10-25 parts of isobornyl acrylate, 8-16 parts of alkyl acrylate, 3-8 parts of modified magnetic filler, 3-6 parts of modified polytetrafluoroethylene, 1-3 parts of photoinitiator, 1-2 parts of antioxidant and 0.1-0.2 parts of colorant.
2. The ultra-long-lasting UV coating of the proportional valve spool armature according to claim 1, characterized in that: The preparation method of the modified magnetic filler comprises the following steps: The magnetic filler and anhydrous ethanol are mixed, a coupling agent is added, the mixture is heated to 50-65° C., stirred for reaction for 2-4 hours, cooled, filtered, and dried to obtain a modified magnetic filler.
3. The ultra-long-lasting UV coating of the proportional valve spool armature according to claim 1, characterized in that: The preparation method of the modified polytetrafluoroethylene comprises the following steps: S1. The silane coupling agent and anhydrous ethanol are mixed, stirred, added to the polypropylene fiber, soaked, filtered, washed, and dried to obtain a modified polypropylene fiber; S2. The modified polypropylene fiber, hydroxylated carbon nanotubes and anhydrous ethanol obtained in step S1 are mixed, heated and stirred to obtain a mixed solution; S3. Add polytetrafluoroethylene to the mixed solution obtained in step S2, stir, grind, and spray-dry to obtain modified polytetrafluoroethylene.
4. The ultra-long-lasting UV coating of the proportional valve spool armature according to claim 3, characterized in that: In the step S2, the mass ratio of the modified polypropylene fiber to the hydroxylated carbon nanotube is (1.3-2):
1.
5. The ultra-long-lasting UV coating of the proportional valve spool armature according to claim 3, characterized in that: In step S3, the mass ratio of polytetrafluoroethylene to the hydroxylated carbon nanotubes in the mixed solution is (8-11):
1.
6. The ultra-long-lasting UV coating of the proportional valve spool armature according to claim 1, characterized in that: The preparation method of the antioxidant comprises the following steps: Q1. Add 3,5-di-tert-butyl-4-hydroxybenzoic acid and chloroform into a reaction kettle, add dichlorothionyl dropwise under an inert gas atmosphere, heat to 45-55°C, react at a constant temperature for 5-6 hours, and distill under reduced pressure to obtain 3,5-di-tert-butyl-4-hydroxybenzoyl chloride; Q2. Add 3,5-di-tert-butyl-4-hydroxybenzoyl chloride, tri(4-chlorophenyl)methane and sodium hydroxide obtained in step Q1 into the reaction kettle in sequence, heat to 30-45°C and react for 4-8h, cool, wash and dry to obtain an antioxidant.
7. The ultra-long-lasting UV coating of the proportional valve spool armature according to claim 6, characterized in that: The molar ratio of the 3,5-di-tert-butyl-4-hydroxybenzoic acid to tri(4-chlorophenyl)methane is (3.2-3.8):
1.
8. The ultra-long-lasting UV coating of the proportional valve spool armature according to claim 1, characterized in that: The colorant is any one or more of titanium dioxide, chromium oxide green, cobalt blue, inorganic brown and zinc chrome yellow.
9. The ultra-long-lasting UV coating of the proportional valve spool armature according to claim 1, characterized in that: The diisocyanate is selected from any one or more of isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate and toluene diisocyanate.
10. A method for preparing an ultra-long-lasting UV coating of a proportional valve core armature as claimed in any one of claims 1 to 9, characterized in that: The following steps are included:
1. mixing diisocyanate, polytetramethylene glycol, hydroxyethyl acrylate, hydroxyethyl methacrylate, isobornyl acrylate, alkyl acrylate, modified magnetic filler, modified polytetrafluoroethylene, photoinitiator, antioxidant and colorant to obtain a primary mixture; 2. Grind the primary mixture obtained in step 1 by a three-roll mill, spray or apply it on the valve core armature of the proportional valve, and cure it by UV to obtain a UV coating.
Citation Information
Patent Citations
Surface microstructure coating process of self-extinction UV coating and application thereof
CN111744751A
Wear-resistant water-based polyurethane paint and preparation method thereof
CN108977026A
Nano particle modified UV curing coating as well as preparation method and application thereof
CN116179073A
High-weather-resistance powder coating and preparation method thereof
CN117683443A
Soft-light water-based photocureable coating and preparation method thereof
CN117903683A
